Anti-austerity riots in late developing states: Evidence from the 1977 Egyptian Bread Intifada - Ketchley, N; Eibl, F; Gunning, J (SAGE Publications, 2023)
In late developing states, labor markets are often segmented as a result of import substitution and political coalitions centered on the formally employed. Building on insider–outsider and moral economy frameworks from political economy, we theorize that in such contexts labor market insiders develop strong expectations about welfare provision and public transfers that make them more likely to riot against proposed austerity measures. We test our argument with the case of Egypt during the 1977 Bread Intifada, when the announcement of subsidy cuts sparked rioting across the country. To conduct our analysis, we match an original event catalog compiled from Arabic-language sources with disaggregated employment data. Spatial models, rich micro-level data, and the sudden and short-lived nature of the rioting help us to disentangle the importance of an area’s labor force from its location and wider socio-economic context. As we show, despite the diffuse impact of the subsidy cuts, rioting was especially concentrated in areas with labor market insiders – and this is after accounting for a range of plausible alternative explanations. The results suggest that moral economies arising from labor market segmentation can powerfully structure violent opposition to austerity.